Investigation of liquefaction‐induced lateral spreading of gently sloping grounds using a variable permeability model. (29th May 2021) - Malekmakan, Mahmood; Shahir, Hadi; Ayoubi, Peyman
Abstract: Liquefaction‐induced lateral spreading takes place on gently sloping grounds due to the liquefaction of sand layers during an earthquake. This phenomenon had catastrophic effects in past events such as the 1964 Niigata, Japan earthquake. In this study, a recently proposed variable permeability function along with a critical state two‐surface plasticity model is employed in a fully‐coupled dynamic numerical model to simulate the lateral spreading. The variable permeability function is re‐calibrated such that the numerical model is able to simulate lateral spreading in a more realistic way compared to the experimental records. By means of six centrifuge experiments for verification, it is shown that the current numerical model is properly capable to capture the underlying physics of liquefaction‐induced lateral spreading. Using the calibrated model, a comprehensive parametric study is conducted and the results are used to develop a practical correlation to estimate the lateral displacement of a liquefied gently sloped ground.